Antagonist of microRNA-21 improves balloon injury-induced rat iliac artery remodeling by regulating proliferation and apoptosis of adventitial fibroblasts and myofibroblasts - Wang, Fei; Zhao, Xue-Qiang; Liu, Jun-Ni; Wang, Zhi-Hao; Wang, Xiu-Ling; Hou, Xiao-Yang; Liu, Rong; Gao, Fei; Zhang, Ming-Xiang; Zhang, Yun; Bu, Pei-Li (Journal of cellular biochemistry, 2012)
Molecular pathways involved in adventitial fibroblasts (AFs) and myofibroblasts (MFs) proliferation and apoptosis contribute to vascular remodeling. MicroRNA‐21 (miR‐21) plays an important role in regulating cellular proliferation and apoptosis of many cell types; however, the effect of miR‐21 on AFs and MFs is still unknown. In this study, we found that miR‐21 was expressed in AFs and overexpressed in MFs. Inhibition of miR‐21 decreased proliferation and increased apoptosis of AFs and MFs, and overexpression of miR‐21 with pre‐miR‐21 had the reverse effect. Programmed cell death 4 (PDCD4), related to cell proliferation and apoptosis, was validated as a direct target of miR‐21 by dual‐luciferase reporter assay and gain and loss of function of miR‐21 in AFs and MFs. PDCD4 knockdown with siRNA partly rescued the reduced proliferation with miR‐21 inhibition and alleviated the increased apoptosis induced by miR‐21 inhibition in AFs and MFs. Moreover, increasing PDCD4 expression by miR‐21 inhibition significantly decreased JNK/c‐Jun activity. In contrast, decreasing PDCD4 expression by pre‐miR‐21 treatment increased JNK/c‐Jun activity, while the effect of miR‐21 inhibition on JNK/c‐Jun activity could be rescued by PDCD4 siRNA. Moreover, miR‐21 inhibition could regulate proliferation and apoptosis of vascular AFs and MFs in vivo. Furthermore, miR‐21 inhibition reversed vascular remodeling induced by balloon injury. In summary, our findings demonstrate that miR‐21 may have a critical role in regulating proliferation and apoptosis of AFs and MFs, and PDCD4 is a functional target gene involved in the miR‐21‐mediated cellular effects in vascular remodeling by a miR‐21/PDCD4/JNK/c‐Jun pathway. J. Cell. Biochem. 113: 2989–3001, 2012. © 2012 Wiley Periodicals, Inc.